2019
DOI: 10.1002/ldr.3435
|View full text |Cite
|
Sign up to set email alerts
|

Arid ecosystem resilience to total petroleum hydrocarbons disturbance: A case‐study from the State of Kuwait associated with the Second Gulf War

Abstract: The world's largest hydrocarbon disturbance occurred in the deserts and offshore waters of Kuwait during the Second Gulf War in 1990–1991. In this research, remote sensing (RS) and geographic information system (GIS) techniques were utilized to explore how native desert vegetation has recovered from hydrocarbon contamination after the Second Gulf War. By using RS techniques, change detection analysis was conducted to understand the changes about the coverage and extent of the total petroleum hydrocarbon (TPH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…It is also considered the most widely used index for assessing vegetation dynamics at the local, regional, and global scales [ 63 ]. Our previous work showed consistent results in determining native desert vegetation in the State of Kuwait [ 12 , 55 , 64 ]. The following Equation was implemented to generate the NDVI layer: …”
Section: Methodssupporting
confidence: 67%
“…It is also considered the most widely used index for assessing vegetation dynamics at the local, regional, and global scales [ 63 ]. Our previous work showed consistent results in determining native desert vegetation in the State of Kuwait [ 12 , 55 , 64 ]. The following Equation was implemented to generate the NDVI layer: …”
Section: Methodssupporting
confidence: 67%
“…The recovery of such native desert plant communities could be associated with the soil type, geomorphological features, and total petroleum hydrocarbon (TPH)-contamination at the sites. Vegetation regrowth was higher at Petrocalcid soils in Umm Gudair sites [ 12 ], which store high quantities of water, potentially making it available for plant uptake during dry periods [ 13 ]. Petrogypsid soils also show good potential for vegetation growth at Wadi Al Batin [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation regrowth was higher at Petrocalcid soils in Umm Gudair sites [ 12 ], which store high quantities of water, potentially making it available for plant uptake during dry periods [ 13 ]. Petrogypsid soils also show good potential for vegetation growth at Wadi Al Batin [ 12 ]. The regrowth of some native desert plants was observed over a layer of clean sediment covering the oil layers, as massive remobilization of sand sheets was found in the oil-affected areas (Koch and Le-Baz 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Suitable phytoremediation management procedures require a good understanding of native plant species response to hydrocarbon contamination. Abdullah et al (2020) assessed the ecosystem resiliency to total petroleum hydrocarbon (TPH) contamination in Kuwait using remote sensing and GIS. This study found that autogenic recovery of native desert plants occurred within a few years as 34% of the TPH contaminated areas were re-colonised with native desert plants.…”
Section: Introductionmentioning
confidence: 99%